2007
DOI: 10.1016/j.jala.2006.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Microbioreactors for Bioprocess Development

Abstract: As a step toward high-throughput bioprocess development, we present design, fabrication, and characterization of polymer based microbioreactors integrated with automated sensors and actuators. The devices are realized, in increasing levels of complexity, in poly(dimethylsiloxane) and poly(methyl methacrylate) by micromachining and multilayer thermal compression bonding procedures. Online optical measurements for optical density, pH, and dissolved oxygen are integrated. Active mixing is made possible by a minia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 47 publications
0
52
0
3
Order By: Relevance
“…Zhang et al (85) reported a yield of biohydrogen of 57 ml·g -1 when cornstalk was treated with sodium hydroxide (0.5 % naoh); this value was 19-fold higher than the yield obtained from untreated materials (3 ml·g -1 ). Furthermore, the authors investigated the production of biohydrogen from cornstalk waste with mixed pretreatments of acid (0.2 % hcl) and heat, with a maximum yield of 150 ml·g -1 , or a 50 times increase as compared to the initial value, thus proving the efficiency of both acid and base pretreatment methods.…”
Section: Biohydrogen Production From Agricultural Wastesmentioning
confidence: 94%
See 2 more Smart Citations
“…Zhang et al (85) reported a yield of biohydrogen of 57 ml·g -1 when cornstalk was treated with sodium hydroxide (0.5 % naoh); this value was 19-fold higher than the yield obtained from untreated materials (3 ml·g -1 ). Furthermore, the authors investigated the production of biohydrogen from cornstalk waste with mixed pretreatments of acid (0.2 % hcl) and heat, with a maximum yield of 150 ml·g -1 , or a 50 times increase as compared to the initial value, thus proving the efficiency of both acid and base pretreatment methods.…”
Section: Biohydrogen Production From Agricultural Wastesmentioning
confidence: 94%
“…A microbioreactor must possess similar characteristics to a bench-scale bioreactor in terms of fermentation conditions, feedback control loops (18,23,31,46), product quality and yield. Recently, some of these reactors have been enhanced with the capability to monitor and control parameters such as optical density (oD), ph, temperature and dissolved oxygen (Do) online and in real time and thereby avoid the need for sample removal (85). the optical sensor technologies have been applied to these bioreactors for online monitoring.…”
Section: Miniaturized Bioreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances of automated cell culturing are combining microelectronics, micromechanics, micro-optics, communication technologies, microfluidics and assembly technology, which has lead to a number of miniaturized devices [1][2][3]. Many scientific publications can be found in which integrated complicated systems are studied, while in hospitals or in fertility clinics the procedures are still predominantly based on Petri dishes.…”
Section: Motivationmentioning
confidence: 99%
“…Ainda, em tais ensaios há possíveis contaminações cruzadas e exigem de maior quantidade de energia devido ao tamanho dos equipamentos envolvidos (Kumar et al, 2004;Zhang et al, 2007;Au et al, 2011;Hegab et al, 2013). Assim, o desenvolvimento de bioprocessos pode ser otimizado com a utilização da microfluídica geradora de gradiente difusivo, podendo avaliar o crescimento celular frente a diferentes condições, realizar análises em tempo real por meio de sensores integrados, e obter resultados comparáveis aos processos convencionais, em um único dispositivo microfluídico (Hegab et al, 2013).Embora apresente um alto potencial investigativo, a microfluídica com geração de gradiente difusivo ainda é pouco explorada no campo da microbiologia industrial.…”
Section: Introductionunclassified